Venomics of scorpion Ananteris platnicki (Lourenço, 1993), a New World buthid that inhabits Costa Rica and Panama - Díaz Oreiro, Cecilia (2024)
Ananteris is a scorpion genus that inhabits dry and seasonal areas of South and Central America. It is located in a distinctive morpho-group of Buthids, the ‘Ananteris group’, which also includes species distributed in the Old World. Because of the lack of information on venom composition, the study of Ananteris species could have biological and medical relevance. We conducted a venomics analysis of Ananteris platnicki, a tiny scorpion that inhabits Panama and Costa Rica, which shows the presence of putative toxins targeting ion channels, as well as proteins with similarity to hyaluronidases, proteinases, phospholipases A2, members of the CAP-domain family, and hemocyanins, among others. Venom proteolytic and hyaluronidase activities were corroborated. The determination of the primary sequences carried out by mass spectrometry evidences that several peptides are similar to the toxins present in venoms from Old World scorpion genera such as Mesobuthus, Lychas, and Isometrus, but others present in Tityus and Centruroides toxins. Even when this venom displays the characteristic protein families found in all Buthids, with a predominance of putative Na+-channel toxins and proteinases, some identified partial sequences are not common in venoms of the New World species, suggesting its differentiation into a distinctive group separated from other Buthids.